Twinning and stacking fault-induced precipitation in an aluminum alloy - Yabo Fu; Vahid Yousefi Mehr; Mohammad Reza Toroghinejad; Xizhang Chen; Jinchuan Jie; Shijie Zhu (Journal of Materials Research and Technology)
The precipitation process in Al alloys has been an attractive phenomenon for engineering alloys. In this study, the Al 6082 alloys processed via forging, followed by a heat treatment procedure consisting of solution treatment at 530 °C for 3 h, and an aging process at 175 °C for 8 h. Detailed precipitation investigations have been conducted using high-resolution TEM. The results show that the Al, Mn, and Si elements segregate to form precipitates with complex crystal structures at different locations such as triple junctions. Also, two major scenarios for determining precipitation formation during heat treatment are proposed. The single atom jump along the interface between the precipitate and the matrix is evidenced by the creation of a jagged interface. The formation of partial dislocations and the resulting staking faults are also suggested as another mechanism in precipitates growth. The creation of twinning adjacent to precipitates and precipitates increased in stacking fault as the atomic layers transformed into closely packed precipitates are observed in sequence.